Methods and means for digital transformation of physical objects - Ivanova, Yoana (Yearbook Telecommunications, 2021)
The research aims to present main methods of digital transformations of physical objects by the means for 3D modelling and 3D scanning. Emphasis is placed on the advantages of laser scanning and the nature of the triangulation methods on which it is based. It is explained how the reliability of the obtained results depends on the calibration process that precedes the 3D scanning of a physical object. Special attention is paid to the technical and software preparation that precedes the 3D scanning process. The practical research is realized using a physical object suitable in terms of construction, shape and size. For the digital transformations is purposefully chosen a real existing spherical robot, which serves as a basis for comparison in assessing the effectiveness of the described methods, as well as the quality and realism of the obtained digital models. The scientific and applied contributions are expressed in a comparative analysis of practical methods, which contains an algorithm of steps suitable for educational purposes for the implementation of the described work processes.